2016
DOI: 10.12988/pms.2016.6713
|View full text |Cite
|
Sign up to set email alerts
|

On distance irregular labeling of ladder graph and triangular ladder graph

Abstract: In this paper, we discussed graph labelings that the distance irregular labeling within which will be presented the results of the distance irregularity strength of ladder graph and triangular ladder graph. The distance irregular labeling on a graph G with v vertices is defined as an assignment λ : V → {1, 2, • • • , k} so that the weights calculated at vertices are distinct. The weight of a vertex x in G is defined as the sum of the labels of all the vertices adjacent to x (distance 1 from x), that is, wt(x) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Chartrand et al (1988) first introduced Irregular labeling in 1988, which developed very rapidly since then. Various types of irregular labeling such as VITL (Anholcer et al, 2009;Bača et al, 2007;Indriati et al, 2016;Baskoro et al, 2010), EITL (Anholcer and Palmer, 2012;) Indriati et al, 2013), totally ITL (Indriati et al, 2020;Marzuki et al, 2013), DVIL (Bong et al, 2017;Novindasari et al, 2016;Slamin, 2017;Sugeng et al, 2021;Susanto et al, 2022a;Susanto et al, 2022b), andDVITL (Wijayanti et al, 2021;Wijayanti et al, 2023). Wijayanti et al ( 2021) define the basic concept of DVITL and tdis(G) and also research some necessary and sufficient conditions for the existence of DVITL (Wijayanti et al, 2023) .…”
Section: Preliminariesmentioning
confidence: 99%
“…Chartrand et al (1988) first introduced Irregular labeling in 1988, which developed very rapidly since then. Various types of irregular labeling such as VITL (Anholcer et al, 2009;Bača et al, 2007;Indriati et al, 2016;Baskoro et al, 2010), EITL (Anholcer and Palmer, 2012;) Indriati et al, 2013), totally ITL (Indriati et al, 2020;Marzuki et al, 2013), DVIL (Bong et al, 2017;Novindasari et al, 2016;Slamin, 2017;Sugeng et al, 2021;Susanto et al, 2022a;Susanto et al, 2022b), andDVITL (Wijayanti et al, 2021;Wijayanti et al, 2023). Wijayanti et al ( 2021) define the basic concept of DVITL and tdis(G) and also research some necessary and sufficient conditions for the existence of DVITL (Wijayanti et al, 2023) .…”
Section: Preliminariesmentioning
confidence: 99%
“…A number of research results on non-inclusive and inclusive d-distance irregularity strengths have been found as seen in [3,4,11,13,14,15,16,17] when d = 1 and in [5,18] when d > 1.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence of this property, he showed that some classes of graphs such as complete bipartite graphs, complete multipartite graphs, stars and trees containing vertex with at least two leaves, have no distance irregular labeling. Novindasari, Marjono and Abusini in [7] determined the distance irregularity strength of ladder graph and triangular ladder graph. Recently, in [2], Bong et al completed the results for the distance irregularity strength of C n and W n , for n ≡ 3, 4, 6, 7 (mod 8).…”
Section: Introductionmentioning
confidence: 99%